The APEV Scale: A Measure of Annual Performance of an Export Venture - Lages, Luis Filipe (2019)
Annual company reports and financial statements rarely distinguish between the domestic and export markets’ operations, and even more rarely provide annual financial indicators on specific export ventures performance. This situation is a major obstacle to the development of export marketing practice and theory. To overcome this state of affairs the authors develop and test a new measure for assessing the annual performance of an export venture (the APEV scale) as perceived by managers. The new measure has five dimensions: 1) annual export venture’s financial performance; 2) annual export venture’s strategic performance; 3) annual export venture’s achievement; 4) contribution of the export venture to annual exporting operations; and 5) satisfaction with annual export venture’s performance. Findings are used to generate managerial implications and directions for future research.